Chemo-bio catalysis using carbon supports: application in H2-driven cofactor recycling - Zhao, X; Cleary, SE; Zor, C; Grobert, N; Reeve, HA; Vincent, KA (Royal Society of Chemistry, 2021)
Heterogeneous biocatalytic hydrogenation is an attractive strategy for clean, enantioselective C=X reduction. This approach relies on enzymes powered by H2-driven NADH recycling. Commercially available carbon-supported metal (metal/C) catalysts are investigated here for direct H2‑driven NAD+ reduction. Selected metal/C catalysts are then used for H2 oxidation with electrons transferred via the conductive carbon support material to an adsorbed enzyme for NAD+ reduction. These chemo-bio catalysts show improved activity and selectivity for generating bioactive NADH under ambient reaction conditions compared to metal/C catalysts. The metal/C catalysts and carbon support materials (all activated carbon or carbon black) are characterised to probe which properties potentially influence catalyst activity. The optimised chemo-bio catalysts are then used to supply NADH to an alcohol dehydrogenase for enantioselective (>99% ee) ketone reductions, leading to high cofactor turnover numbers and Pd and NAD+ reductase activities of 441 h-1 and 2,347 h-1, respectively. This method demonstrates a new way of combining chemo- and biocatalysis on carbon supports, highlighted here for selective hydrogenation reactions.